The Dynamics of Students' Learning Readiness in Primary Schools: A Portrait of Schooling in Rural Areas - Jumasrin Jumasrin (Shautut Tarbiyah, 2020)
This article aims to describe the learning readiness of students in rural areas. With the setting at SDN Pehanggo, the aspects that are explored include: student learning readiness, learning motivation, and parental attention. Through a qualitative approach with a narrative method, this study finds that: first, isolated geographic conditions do not hinder the student's education process, this condition has been going on for generations. The students showed high readiness in learning. Second, the success of the previous people motivated students to achieve success and even obsessed with achieving higher success. Limited learning facilities and facilities do not reduce their enthusiasm for learning, they are even considered a challenge to face. Third, parents pay very high attention to their children's education, as evidenced by their focus on the educational success of their children. As an implication of this study, it is important to point out that isolated geographical conditions in an area are not always a barrier to educational progress. Local communities need to be good models for school-age children to emulate. Likewise, the attention of parents plays an important role in preparing children to learn at school. Children's motivation to learn can be grown from the family by creating a good climate for learning, meeting the learning facilities needed. This study confirms that learning readiness is influenced by learning motivation and parental attention. Keywords:   Learning Readiness, Motivation, Attention of Parents, Rural Areas